Management of Hypertension in Pregnancy - Laura A. Magee; Peter von Dadelszen; Dandan Shi (Wolters Kluwer Health, 2021)
Abstract. Hypertension in pregnancy is currently defined as a systolic blood pressure (BP) of 140 mmHg or more, or a diastolic BP of 90 mmHg or more. This level of BP warrants antihypertensive therapy. Treating to a target BP of 135/85 mmHg halves the risk of severe hypertension that is itself associated with adverse maternal and perinatal outcomes, similar in magnitude to preeclampsia. While based on the results of the Control of Hypertension in Pregnancy Study (CHIPS) trial, this finding is consistent with all antihypertensive trials to date. Also, in the CHIPS trial, "tight" BP control also halved the risk of progression to thrombocytopenia and elevated liver enzymes for the mother, without adverse effects for the fetus or newborn. This was true regardless of the gestational age at which BP control was instituted. While methyldopa, labetalol, and nifedipine are the most commonly-recommended oral antihypertensives, it is not clear that one antihypertensive agent has advantages over the others for treatment of non-severe hypertension in pregnancy. No antihypertensives, including renin-angiotensin-aldosterone system (RAAS) inhibitors, have been shown to be teratogenic, although there may be an increase in malformations associated with the underlying condition of chronic hypertension. Atenolol and RAAS inhibitors should not be used once pregnancy is diagnosed, based on fetotoxicity. At present, BP treatment targets used in clinic are the same as those used at home as the differences are quite variable among hypertensive women. For treatment of acute severe hypertension, the most commonly-recommended antihypertensives are oral nifedipine, IV labetalol, and IV hydralazine, although oral agents have also been shown to be effective in the majority of women; while concerns raised about IV hydralazine-induced maternal hypotension and its consequences have not been confirmed, this medication may be an inferior antihypertensive to oral nifedipine. While treatment recommendations are based on evidence, women should be engaged in decision-making, as their values may alter target BP and antihypertensive choice. Future work will clarify the optimal target BP based on home BP measurements; whether BP targets should be lowered further if the definition of hypertension is based on a lower BP; which, if any, antihypertensive medication for non-severe hypertension is better with regards to maternal and perinatal outcomes; and whether factors beyond BP level (such as variability, race, and other physiological variables) should inform antihypertensive therapy in pregnancy.